Breaking boundaries—coagulation and fibrinolysis at the neurovascular interface - Bardehle, Sophia; Rafalski, Victoria A.; Akassoglou, Katerina (Frontiers in Cellular Neuroscience, 2015)
Blood proteins at the neurovascular unit (NVU) are emerging as important molecular determinants of communication between the brain and the immune system. Over the past two decades, roles for the plasminogen activation/plasmin system in fibrinolysis have been extended from peripheral dissolution of blood clots to the regulation of central nervous system (CNS) functions in physiology and disease. In this review, we discuss how fibrin and its proteolytic degradation affect neuroinflammatory, degenerative and repair processes. In particular, we focus on novel functions of fibrin—the final product of the coagulation cascade and the main substrate of plasmin—in the activation of immune responses and trafficking of immune cells into the brain. We also comment on the suitability of the coagulation and fibrinolytic systems as potential biomarkers and drug targets in diseases, such as multiple sclerosis, Alzheimer’s disease and stroke. Studying coagulation and fibrinolysis as major molecular pathways that regulate cellular functions at the NVU has the potential to lead to the development of novel strategies for the detection and treatment of neurologic diseases.